Application of evidence-based urology in improving quality of care - Arabind Panda; L N Dorairajan; Santosh Kumar (Indian Journal of Urology, 2007)
Evidence-based medicine requires use of the best available evidence for optimal patient care. Increasingly scarce resources and escalating demands on time have led to emphasis on effective treatment. Opinion is slowly yielding to high-quality existent evidence. It is important that urologists adapt to these changes for them to deliver optimum care to the patients. This article discusses the levels of evidence, the nature of desirable evidence, means of assessing quality of clinical trials and meta-analysis and finally the practice of evidence-based urology with special reference to bedside evidence-based urology.